Organic carbon pools and storage in the soil of olive groves of different age. (29th June 2018) - Massaccesi, L.; De Feudis, M.; Agnelli, A. E.; Nasini, L.; Regni, L.; D'Ascoli, R.; Castaldi, S.; Proietti, P.; Agnelli, A.
Abstract : Summary: Compared with annual crop cultivation, tree groves might represent a relevant land‐use system to improve C sequestration, but few data are available to support this hypothesis. To evaluate the potential of olive tree ( Olea europaea L., 1753) cultivation to store soil organic C (SOC), we assessed (i) the distribution of organic C in active (water‐extractable and particulate organic C, WEOC and POC, respectively), intermediate (organic matter associated with stable sand‐size aggregates and silt‐ and clay‐size aggregates, SSAs and SCAs, respectively) and passive (organic matter resistant to oxidation, rSOM) pools, (ii) the phenol content of the C pools, (iii) the humic‐C distribution of the intermediate C pool and (iv) the stocks of SOC pools in two olive groves of different age (7 years (OG7) and 30 years (OG30)) compared with a nearby site with cereal crops (arable soil, AS). In OG30 the organic C stock of the olive grove was no different from that of the AS, but the distribution of SOC pools changed with the age of the olive groves. The WEOC and POC increased in the Ap horizon of OGs, probably because of the herbaceous cover and distribution of chipped prunings on the soil. There were fewer SSAs in OG7 than AS, possibly because of pedoturbations from deep tillage before the olive trees were established, but they increased in OG30. The increase in SSAs and SCAs in the Bw and BC horizons of OG30 was associated with humic‐C and unextractable‐C and a smaller phenol content than AS. This suggested that the olive tree roots had a positive role through rhizodeposition and root turnover, which favoured the stabilization of organic matter into aggregates at depth. In contrast to the active and intermediate C pools, the passive C pool did not vary following the change in land use from arable to olive grove. Highlights: Effects of land‐use change from arable to olive grove on soil organic C pools and stocks. Soil organic C stock increased from 7‐ to 30‐year‐old olive orchard. Olive tree cultivation affected active and intermediate C pools, but not the passive C pool. After 30 years, the olive grove stored an amount of SOC similar to that of the arable system.